Incentive for Sale: § 503(c) and Asset Sales Within the Southern District of New York - Christopher Scavone (Washington University Journal of Law & Policy, 2016)
This Note examines the recent shift towards rejecting proposed Key Employee Incentive Plans within the Southern District of New York as highlighted by the Hawker and Residential Capital decisions, and why the current standard is inadequate to address the special concerns that arose in those two cases. Scavone first examines the historical basis for executive compensation in bankruptcy, the formulation of the 2005 BAPCPA amendments, and the cases that followed. Scavone then presents the Hawker and Residential Capital cases, followed by an analysis of why the application of § 503(c) as it currently stands was inadequate for the proposed asset sales presented in those cases. Scavone argues for adjustments to § 503(c) that better reflect the unique circumstances of those two cases.
Keywords: Key Employee Incentive Plans; § 503(c); New York; Bankruptcy Abuse Prevention and Consumer Protection Act of 2005; bankruptcy; executive compensation